METHOD OF THE BEST AVAILABLE TECHNOLOGY AND LOW CARBON FUTURE OF A COMBINED HEAT AND POWER PLANT - Strušnik, Dušan; Agrež, Marko (Journal of Energy Technology, 2023)
The low-carbon development strategy and ecological awareness of a combined heat and power (CHP) plant is the key factor that enables further development of such systems. CHP plants are subject to rigid European ecological guidelines, which dictate the pace of development of global thermal power engineering. For this purpose, the European Union issued a special Directive for the promotion of heat and power cogeneration, and is established with the best available technology (BAT) method. Even though the production of electricity using carbon-free technologies is on the rise, the production of electricity by fossil fuel combustion cannot be avoided completely. The meaning of the operation of the CHP plant is reflected particularly in the provision of tertiary services to the electric power system, regulation of the network frequency, particularly in winter months, when electricity production using carbon-free technologies is limited. In CHP systems, the low-carbon future is linked intricately to high investment costs and these impacts the final price of energy. Using the BAT method, the article presents the advantages of energy production in a combined heat and power plant, an example of the restructuring of a larger CHP system into a low-carbon plant and guidelines for further development.